+0  
 
+1
157
2
avatar

how would i do this?    2x+3=53x-1

Guest May 4, 2017
Sort: 

2+0 Answers

 #1
avatar+79786 
+2

 

2^(x + 3)  = 5^(3x - 1)  take the log of both sides

 

log 2^(x + 3)  = log 5^(3x - 1)    and we can write

 

(x + 3) log 2  = (3x - 1) log 5     simplify

 

x log 2 + 3 log 2  =  3x log 5 - log 5     rearrange as

 

x log 2 - 3x log 5   =  - 3 log 2 - log 5     multiply through by -1

 

3x log 5 - x log 2  =  3log 2 + log 5   factor the left side

 

x (3 log 5 - log 2)  = 3log 2 + log 5      divide both sides by (3 log 5 - log 2 )

 

x  =  [ 3log 2 + log 5 ] / [ 3 log 5- log 2 ]  ≈   .892

 

 

cool cool cool

CPhill  May 4, 2017
 #2
avatar
+1

Thank You!!!

Guest May 4, 2017

21 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details